Microplastic Bioaccumulation in invertebrates, fish, and cormorants in Lake Champlain - Hammer, Chad; VanBrocklin, Hope (2016)
Student poster, Center for Earth and Environmental Science, SUNY Plattsburgh It is estimated in the United States that 8 trillion microbeads enter our waterways daily. Microplastics are typically discharged into local watersheds through wastewater treatment plant effluent and marine debris, with as much as 1600 synthetic fibers emanating from washing a single piece of clothing. In this project, we assessed microplastic load within Dreissena polymorpha (zebra mussels), Gammarus fasciatus (amphipods), fish, and Phalacrocorax auritus (double-crested cormorants) digestive tracts. Specimens were processed using KOH bath, followed by wet peroxide oxidation digests. Bioaccumulated microplastics were characterized based on type (e.g., fragment, pellet/bead, fiber, film, foam) and size. Results suggest that the majority of microplastics combined for all organisms investigated were fibers (67%), fragments (19%), films (10%), and pellets/beads (4%). No microplastics were observed in zebra mussels. Amphipods contained fibers (50%), fragments (25%), and films (25%). Species-specific trends were observed among fish, specifically Osmerus mordax (rainbow smelt), Cottus cognatus (slimy sculpin), and Micropterus salmoides (large-mouth bass) are primarily consuming fibers. Bluegill sunfish (Lepomis macrochirus) and rainbow smelt were the only species to consume pellets/beads (40%) and films (16%), respectively. Double-crested cormorants contained primarily fibers (78%), as well as films (19%), with minor contributions of pellets/beads and foam. Spatial distribution of microplastic load was greater in rainbow smelt at the most northern and southern sampling sites on Lake Champlain. In freshwater systems, microplastics absorb chemical pollutants and release plasticizers (e.g., carcinogens, neurotoxins, endocrine disruptors) into tissues, with the potential for fitness consequences in wildlife and humans. SUNY Plattsburgh